2021
DOI: 10.1021/acsanm.1c00607
|View full text |Cite
|
Sign up to set email alerts
|

Flowerlike CuO/Au Nanoparticle Heterostructures for Nonenzymatic Glucose Detection

Abstract: The controlled preparation of two-dimensional (2D) nanomaterials exhibiting heterojunction structures based on nontoxic and economical transition metal oxides represents breakthroughs in the electrochemistry field. Herein, flowerlike CuO/Au nanoparticles that have 2D nanomaterial characteristics and excellent glucose sensing performance were prepared by microwave hydrothermal synthesis of sea urchinlike CuO and subsequent self-generated acid etching of the sea urchinlike CuO in the presence of HAuCl 4 and NaBH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 53 publications
0
24
0
Order By: Relevance
“…[23] Recently, Wang et al investigated non-enzymatic glucose detection with CuO/Au nano-particle. [24] Chen et al sensed room temperature NO 2 via CuO nanorods functionalised with Au nanoparticles. [25] The integration of noble metal nano particles significantly improved the electrochemical properties as well as effective cost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23] Recently, Wang et al investigated non-enzymatic glucose detection with CuO/Au nano-particle. [24] Chen et al sensed room temperature NO 2 via CuO nanorods functionalised with Au nanoparticles. [25] The integration of noble metal nano particles significantly improved the electrochemical properties as well as effective cost.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Wang et al. investigated non‐enzymatic glucose detection with CuO/Au nano‐particle [24] . Chen et al.…”
Section: Introductionmentioning
confidence: 99%
“…In the process, the fabricated organic composite electrodes were prone to breaking due to their fragileness. 39 Also, the sensitivity and detection limit of available paper electrodes to glucose 1,[40][41][42][43][44][45][46][47][48] still need to be further improved.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon indicated that the hydrophilic side of the paper electrode was critical to the glucose detection, in agreement with the previous reports. [40][41][42][43][46][47][48]76,77 Possible reasons could be ascribed to the fact that glucose is a polar molecule and has more tendency to adsorb on the hydrophilic back side of the electrode relative to the hydrophobic front side. When the hydrophilic side was shielded with hydrophobic adhesive tape, the possibility of adsorbing glucose on the electrode became low, thus leading to a poor electrochemical performance.…”
mentioning
confidence: 99%
See 1 more Smart Citation